Significance of extracellular vesicles in orchestration of immune responses in Mycobacterium tuberculosis infection - Alipoor, Shamila D.; Elieh-Ali-Komi, Daniel (Frontiers in Cellular and Infection Microbiology, 2024)
Mycobacterium tuberculosis (M.tb), the causative agent of Tuberculosis, is an intracellular bacterium well known for its ability to subvert host energy and metabolic pathways to maintain its intracellular survival. For this purpose, the bacteria utilize various mechanisms of which extracellular vehicles (EVs) related mechanisms attracted more attention. EVs are nanosized particles that are released by almost all cell types containing active biomolecules from the cell of origin and can target bioactive pathways in the recipient cells upon uptake. It is hypothesized that M.tb dictates the processes of host EV biogenesis pathways, selectively incorporating its molecules into the host EV to direct immune responses in its favor. During infection with Mtb, both mycobacteria and host cells release EVs. The composition of these EVs varies over time, influenced by the physiological and nutritional state of the host environment. Additionally, different EV populations contribute differently to the pathogenesis of disease at various stages of illness participating in a complex interplay between host cells and pathogens. These interactions ultimately influence immune responses and disease outcomes. However, the precise mechanisms and roles of EVs in pathogenicity and disease outcomes remain to be fully elucidated. In this review, we explored the properties and function of EVs in the context of M.tb infection within the host microenvironment and discussed their capacity as a novel therapeutic strategy to combat tuberculosis.